Analisis Usaha Penggemukan Sapi Potong Berdasarkan Biaya Produksi - Ani Suryani; Dini Widianingrum; Rachmat Somanjaya (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
Research goals to increase revenue or the welfare of farmers through increased livestock production. Efforts are made is through an increase in population, the application of technology and increasing competitiveness through penerapanmanajemen farm. The research was conducted in the District Kasokandel Majalengka district with the survey method. The unit of analysis is the peasant farmers who carry out analysis of samples of beef cattle fattening to strata ownership 1-4 tails 16 people, strata ownership 5-8 tails of 7 people. The results showed that the analysis of fattening beef cattle in Sub District Kasokandel Majalengka is a side business with an average ownership of two birds per person. Nation's beef cattle are kept the nation Peranakan Ongole (PO) to the level of implementation of maintenance management is quite good except going, cages, feed and medicines. Revenue analysis of fattening beef cattle in Sub District Kasokandel Majalengkayang highest with the scale of 5-8 tails and 1-4 tail respectively and Rp 2,381,750.00 Rp 3,880,228.00. The conclusion was analysis of the beef cattle fattening business in Kasokandel District, Majalengka Regency, which is a side business with an average ownership of 2 head per person and total ownership of 1-4 head amounting to IDR 2,381,750, total ownership of 5-8 head amounting to IDR 3,880,228.60.